MEDNET – an approach to facial micro-emotion recognition using pixel binning and local Binary pattern - convolutional neural network - Araf, Tashreef Abdullah (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Science in Computer Science and Engineering, 2023.